2015
DOI: 10.1017/thg.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Does Breastfeeding Behavior Run in Families? Evidence From Twins, Their Sisters and Their Mothers in the Netherlands

Abstract: The aim of the present article was to study the prevalence and the heritability of the initiation of breastfeeding in the Netherlands. The study was carried out in 5,581 participants from the Netherlands Twin Register, and included female twins, their sisters and mothers. All of the participants were born between 1911 and 1991. Breastfeeding was self-reported by the participants, and its prevalence was estimated conditional on birth cohort (born before 1955, 1955-1964, 1965-1974, 1975, or later). To estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…36,37 Finally, twin studies provide evidence that breastfeeding practices are partly heritable. 40,41 Therefore, differences in breastfeeding practices may reflect differences in genetics, which could contribute to their associations with ALL and AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Finally, twin studies provide evidence that breastfeeding practices are partly heritable. 40,41 Therefore, differences in breastfeeding practices may reflect differences in genetics, which could contribute to their associations with ALL and AML.…”
Section: Discussionmentioning
confidence: 99%
“…Although the hypotheses put forward to explain the reduced risk of leukemia among breastfed children were proposed in the context of B‐ALL, 29 breast milk constituents also interact with myeloid cells, supporting a potential mechanistic role for breastfeeding in the prevention of AML 36,37 . Finally, twin studies provide evidence that breastfeeding practices are partly heritable 40,41 . Therefore, differences in breastfeeding practices may reflect differences in genetics, which could contribute to their associations with ALL and AML.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that breastfeeding and lactation itself are heritable traits. In previous twin studies, the heritability of initiation of breastfeeding ranged from 49% [128] to 70% [129]. DNA-methylation profiles may be influenced by several early life factors.…”
Section: Discussionmentioning
confidence: 99%
“…Three different twin and family studies from diverse cultural backgrounds (Spain, Australia and The Netherlands) have found significant heritability estimates (44–70%) for initiation and duration of breastfeeding behaviour (Colodro-Conde, Sanchez-Romera, & Ordonana, 2013; Colodro-Conde et al, 2015; Merjonen, Dolan, Bartels, & Boomsma, 2015). This means that approximately half of the inter-individual variability observed in the behaviour of breastfeeding is due to differences in genetic makeup, and the other half is due to differences in environmental related experiences.…”
Section: Introductionmentioning
confidence: 99%